A qualitative study to understand patients' experiences of their post-operative outcomes following forefoot surgery. Issue 3 (June 2022) - Dismore, Lorelle Louise; van Wersch, Anna; Critchley, Rebecca; Murty, Aradhyula; Swainston, Katherine
Background: Hallux valgus and hallux rigidus are two common forefoot conditions causing deformity, pain, functional limitations, disability and deteriorating health status resulting in the requirement for surgery. Even when surgery is performed by an experienced surgeon, there remains a potential for patients to experience dissatisfaction and unfavourable outcomes. Adverse results are moderated by psychosocial variables; however, there is a paucity of qualitative research providing insight into how patients perceive their outcomes and the factors affecting their recovery. Objective: The study aimed to qualitatively explore patients' experiences of their surgical outcomes following forefoot surgery and factors associated with their recovery. Semi-structured interviews with 15 patients who received surgery for hallux valgus and/or hallux rigidus were conducted. Results: Thematic analysis generated five themes: physical limitations, the psychosocial impact of surgical recovery, regaining normality, patients' expectations for physical recovery and an altered body-image. Physical and psychosocial factors were inter-related. Patients experiencing problematic outcomes were functionally limited, had low mood and were unable to return to a normal life post-surgery. The women reported weight related issues and were limited in their footwear and clothing choices, negatively impacting on their self-esteem. Conclusion: A forefoot condition is multifaceted, with patients experiencing a range of physical and psychological factors that may influence their outcomes and recovery from surgery. Patients need to be supported holistically with the use of a biopsychosocial model. A multidisciplinary approach to care and treatment within the forefoot surgical pathway with the inclusion of allied health professionals will enable to better support patients to enhance their outcomes.